Considerations for Assessing the Appropriateness of High-Cost Pediatric Care in Low-Income Regions - Argent, Andrew C. (Frontiers in Pediatrics, 2018)
It may be difficult to predict the consequences of provision of high cost pediatric care (HCC) in low and middle-income countries (LMICs), and these consequences may be different to those experienced in high income countries. An evaluation of the ethics of high cost pediatric care in LMICs must incorporate considerations of the specific context in that country (population age profile, profile of disease, resources available); likely costs of the HCC; likely benefits that can be gained vs the costs that will be incurred. Ideally the process that is followed in decision making around HCC should be transparent, and should involve the communities that will most affected by those decisions. It is essential that the impacts of provision of HCC are carefully monitored so that informed decisions can be made about future provision medical interventions.